Organizational Flexibility and Its Impact on Organizational Effectiveness - Taghreed Khalil Ibrahim (Research Parks Publishers, 2026)
The purpose of the study is to determine how organizational flexibility affects how well the QaisKoba factory produces food goods. To this purpose, organizational flexibility was classified as an independent variable, and work satisfaction, productivity, and goal achievement were designated as dependent variables of organizational effectiveness. A questionnaire with a sample of 25 administrative leaders from the QaisKoba factory was utilized to test the research assumptions. The statistical application SPSS was used to extract the data. The study came to a number of conclusions, the most notable of which being that organizational flexibility has an impact on organizational success in various dimensions and is correlated with it.